Descemet Membrane Endothelial Keratoplasty in Eyes with an Artificial Iris - Keye, Philip; Reinhard, Thomas; Maier, Philip Christian (Klinische Monatsblätter für Augenheilkunde, 2023)
The purpose of this study is to report the outcome of Descemet membrane endothelial keratoplasty (DMEK) in three eyes with a complex anterior segment and an artificial iris. A retrospective chart review of three cases was performed and clinically meaningful patient characteristics, clinical events, and therapeutic interventions were outlined. A literature search was performed and the clinical course of the three cases was discussed in the context of the published literature. DMEK in the presence of an artificial iris did not match the clinical results of DMEK in uncomplicated eyes. All three eyes experienced major complications, such as failure to achieve graft adherence, early graft failure, or an immune reaction. The indication for DMEK in complex anterior segments with an artificial iris should be made with the awareness of multiple possible complications and the potentially poor prognosis of the procedure.
Keywords: DMEK; artificial iris; iris prothesis; keratoplasty; cornea